Informants and the Fourth Amendment: A Reconsideration - Tracey Maclin (Washington University Law Quarterly, 1996)
This Article argues that the Court's current interpretation of the Fourth Amendment, which sanctions the government's authority to insert secret spies and informants into our lives, is misguided. Part I highlights the historical background of the Fourth Amendment to show why its procedural safeguards are relevant when considering whether the government should be free of constitutional restraint when deploying informants and spies in our homes and offices. Part II will explain and critique the Court's cases on informants. Part III contends that the Court's doctrine on informants rests on a fallacious conception of privacy. As an alternative to the current approach, I argue that the government's authority to use informants and secret agents can and should be controlled by the Warrant Clause of the Fourth Amendment. Police operations involving the planting of informants in a home or the recording of private conversations should be subject to the same constitutional restraints that currently control governmental wiretapping and bugging. My conclusion that the procedural safeguards of the Warrant Clause should regulate the use of informants stems from the belief that the central meaning of the Fourth Amendment is distrust of police power. As the law exists today, the police can decide for themselves who will be targets of secret surveillance. Such untrammeled police power is at odds with the values that inspired the Fourth Amendment.
Keywords: Electronic surveillance; Informers